Regulacje prawne w zakresie opieki okołoporodowej w Polsce w kontekście projektu nowego standardu organizacyjnego - Witek, Zuzanna (Wydawnictwo Naukowe UAM, 2018)
Pursuant to Article 68(3) of the Constitution of the Republic of Poland, a pregnant woman is entitled to special care from the State. Therefore, it seems extremely important to indicate uniform, universally binding standards in order to improve the quality of services provided and to respect the fundamental rights due to women and their children in maternity care. Unfortunately, as the analysis and reports concerning the observance of patients’ rights during the perinatal period show, the current standards are not always properly implemented by medical institutions, and the legal guarantees of observance of perinatal care standards are not sufficient. The aim of the article is to discuss the legal regulations in force in the field of perinatal care, to indicate their subject and subject scope and to conduct a legal analysis of the proposal of new organisational standards of perinatal care, which are to enter into force as of 1 January 2019. The basis for the discussion is the presentation of the legal form of the existing standards of perinatal care. It is extremely important to answer the question whether the principles of medical knowledge should be enacted in the form of standards of medical procedure in the form of universally binding normative act, or whether they should constitute guidelines and recommendations that are legally non-binding. Perinatal care standards in the context of the duty of doctors and medical staff to apply current medical knowledge and to act with due diligence deserves additional attention. The article contains a detailed analysis of the proposal of new standards and presents de lege ferenda postulates, especially in the field of legal guarantees of observance of perinatal care standards in Poland.
Legal regulations concerning perinatal care in Poland in the context of the draft of a new organisational standard
Keywords: perinatal care standards; perinatal care; medical management stand; ards; patient’s rights